Micropropagation of Vanasushava pedata - An Endangered Medicinal Plant of South India - Karuppusamy, S; Kiranmai, C; Aruna, V; Pullaiah, T (Plant Tissue Culture and Biotechnology, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> An efficient in vitro propagation of an endangered medicinal plant Vanasushava pedata (Apiaceae) by axillary shoot proliferation from nodal segments of mature plants was designed. The medium type and growth regulators markedly influenced in vitro regeneration of V. pedata. An in vitro plantlet production system has been investigated on MS with the synergistic combination of BA (5.0 mg/l), IAA (0.1 mg/l) and 3 % sucrose which promoted the maximum number of shoots (8.6) as well as enhanced shoot lengths. Subculturing of nodal segments from in vitro derived shoots on a similar medium enabled continuous production of healthy shoots with a similar frequency. Rooting was highest (100%) on half strength MS containing IAA (2.0 mg/l). Micropropagated plants established in garden soil and forest humus (1 : 1) were uniform and identical to the donor plants with respect of growth characteristics as well as floral features. These in vitro-raised plants grew normally in greenhouse and natural habitat without showing any morphological variation. Â Key words: Vanasushava pedata, Medicinal plant, Nodal explants, Micropropagation, Successful acclimation DOI = 10.3329/ptcb.v16i2.1109 Plant Tissue Cult. & Biotech. 16(2): 85-94, 2006 (December)